Effects of UK hostile environment policies on maternity care for refugees, asylum seekers, and undocumented migrants in Camden: Examining the experiences of healthcare professionals and community organisations - Poppy Pierce; Haleema Adil; Tiffany Kwok; Catherine Cooke; Deveney Bazinet; Kate Roll; Sara L Hillman (Journal of Migration and Health)
Background: The London borough of Camden has long been home for many refugees, asylum seekers, and undocumented migrants (RASUs). Over time, it has witnessed an increase in the population of these migrant groups, accompanied by notable changes in the obstacles they encounter when seeking health services, particularly maternity care. We explore how the ‘hostile environment’ policies affect access to and delivery of quality maternity services for RASUs. Methods: This study was conducted over eight months (November 2021–July 2022) both remotely and face-to-face, in various locations in Camden and in the Maternity Department at University College London Hospital, UK. Healthcare professionals (HCPs) and community organisations (COs) were identified as two major stakeholders involved in the care provision for RASUs. 33 semi-structured interviews were conducted (with 22 HCPs and 11 COs) to understand their experiences of delivering care to this population. Results: There was consensus among HCPs and COs that the current immigration policies undermined their duty of care, personal morals, and the principles of the NHS. These policies have created a restrictive environment, making it increasingly difficult for migrants to navigate the healthcare system and creating an atmosphere of distrust, propagating fears of being charged. This has led to HCPs and COs going beyond their remits to ensure that RASUs are accessing and engaging with maternity care, regardless of an individual's status and despite any potential repercussions for themselves. Conclusion: In the face of an intensifying hostile environment under the UK government, supporting RASUs cannot be solely reliant on political measures. We need to advocate for healthcare navigator roles, health justice partnerships, specialist teams, and comprehensive training for service providers. HCPs and COs should be adequately supported in their endeavours to ensure RASUs have access to standardised, high-quality maternity care.